ANALYSIS OF THE NEED FOR INTERNET OF THINGS CURRICULUM IN VOCATIONAL HIGH SCHOOLS: A Case Study of SMK Negeri 1 Kupang - Daniela Bisik; Khatrin J. Takuneno (Journal of Innovative Technologies in Learning and Education, 2024)
Internet of Things (IoT) education at the vocational school level can be well-integrated with other industries in order to enable students who are trained here to develop expertise and meet future demand in various industries. The study was conducted by analyzing the needs and constraints faced by SMK Negeri 1 Kupang in applying a smart education in learning IoT technology on the program of Technology and Network Engineering (TJKT). The present study followed a qualitative research approach and data were collected through interviews from teachers and students, school infrastructure assessment. The findings reveal significant curriculum gaps, inadequate resources and the unpreparedness of teachers to deliver IoT education. However, students expressed high levels of motivation to engage with IoT topics. The study concludes that, successful IoT education requires updating curriculum, developing specialized teachers, and enhancing infrastructure of vocational schools. By leveraging affordable IoT tools and fostering industry partnerships, schools can provide students with the practical skills needed to thrive in IoT-enabled industries.